Nursing and health - Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
Human population suffers from the omissions in the field of assistance, at various levels of health care, despite the current political, social and technological advances, whether global or national. Therefore, we believe that the speech of those who occupy places that allow raising the representative voice of the professionals who form the health team, need greater strength so that transformations happen in practice.